Ionic conductivity and conduction mechanism studies on cellulose based solid polymer electrolytes doped with ammonium carbonate - M. I. H. Sohaimy; M. I. N. Isa (Springer-Verlag Berlin Heidelberg, 2024)
Indexed by SCOPUS